Impact of the COVID-19 pandemic on cerebral venous sinus thrombosis in China: a comparative study - Xiaoming Zhang; Kun Fang; Duo Lan; Xiangqian Huang; Xunming Ji; Ran Meng; Da Zhou (BMC Neurology)
Abstract Background Cerebral venous sinus thrombosis (CVST) is a rare yet significant neurological disorder with high mortality. Understanding its evolving characteristics, risk factors, and outcomes, particularly in Chinese patients after the COVID-19 pandemic, is critical for developing effective preventive and therapeutic strategies. Methods A retrospective analysis was conducted on 471 CVST cases from Xuanwu Hospital, comparing data before (2013–2017, n = 243) and after (2021–2023, n = 228) the COVID-19 pandemic. Data on demographics, clinical features, risk factors, and outcomes were evaluated, with subgroup analyses based on gender and age. Results The mean patient age was 38 ± 14 years, with a female preponderance (55.0%). After the COVID-19 pandemic, significant changes in symptoms and neuroimaging findings were observed, including increased visual impairment and decreased headache, neurological deficits, and seizures. Infection emerged as a prominent risk factor, including eight cases related to COVID-19 or vaccination. At discharge, favorable outcomes (mRS 0–2) were noted in 86.6% of patients. Poor outcomes were associated with central nervous system (CNS) infection, oral contraceptive use or hormone replacement therapy (HRT), hematologic disorders, anemia, and prothrombotic conditions. Anemia was identified as an independent predictor of survival. Conclusions The pandemic has significantly altered the clinical and epidemiological profile of CVST in China. Infections have emerged as key risk factors, while anemia remains a critical prognostic indicator. These findings highlight the need for targeted clinical strategies to improve outcomes. Trial registration This study protocol was reviewed and approved by the ethics committee of Xuanwu Hospital, Capital Medical University (No. 2022-004, dated on November 20, 2022). The clinical trial was registered at Chinese Clinical Trial Registry (ChiCTR2200057621).